The Effectiveness of Rope Bottom Media in Improving Volleyball Underhand Passing Ability - Tantowi Jauhari; Mohamad Da'i; Hilmy Aliriad; Afdol Febriansyah (Journal of Physical Education Health and Sport, 2026)
Underhand passing is one of the important basic techniques in volleyball that must be mastered by elementary school students, but observations show that students' ability to control the direction and bounce of the ball is still low. This study aims to determine the effectiveness of using Rope Bottom media in improving elementary school students' underhand passing abilities. This study used an experimental method with a pre-experimental one-group pretest–posttest design. The study population was 30 students who participated in volleyball extracurricular activities, with a sample of 15 students selected using a purposive sampling technique. The instrument used was a 60-second underhand passing test with a scoring system based on the number of valid bounces in the target box. Data analysis was carried out through descriptive statistics, the Shapiro–Wilk normality test, paired sample t-test, and Cohen's d effect size calculation using IBM SPSS Statistics. The results showed an increase in the average score from 11.87 in the pretest to 23.07 in the posttest. The paired sample t-test showed a significance value of <0.05, which means there was a significant difference between before and after treatment. The very large effect size indicates that the Rope Bottom media has a strong influence in improving students' underhand passing ability. Therefore, it can be concluded that the use of Rope Bottom media is effective in improving elementary school students' underhand passing ability and can be an alternative, innovative, and applicable physical education learning medium.